Newton and the Origin of Civilization - Buchwald, Jed Z. (Book collections on Project MUSE., 2013)
Isaac Newton's Chronology of Ancient Kingdoms Amended, published in 1728, one year after the great man's death, unleashed a storm of controversy. And for good reason. The book presents a drastically revised timeline for ancient civilizations, contracting Greek history by five hundred years and Egypt's by a millennium. Newton and the Origin of Civilization tells the story of how one of the most celebrated figures in the history of mathematics, optics, and mechanics came to apply his unique ways of thinking to problems of history, theology, and mythology, and of how his radical ideas produced an uproar that reverberated in Europe's learned circles throughout the eighteenth century and beyond.